Tools for internationalisation and increasing institutional trust to authorities in the international contingent environment of domestic universities in the transformation conditions of the digital environment - V. V. Bondarenko; E. V. Kuznetsova (Цифровая социология)
The article describes methodological provisions on the tools’ use for internationalizing the activities of Russian universities and on increasing institutional trust among the international contingent in the context of global digitalization. The authors provide a detailed description of the digital environment use to achieve the goals of promoting Russian education on the world market and activating “soft power”. The article identifies problems in the field of universities’ digital IT infrastructure that create certain difficulties for the implementation of education in a digital environment and negatively affect the competitiveness of Russian education. The study presents methodological approaches both for preventing the possibility of the possible emergence of a sociocultural gap and intercultural dissonance, and for transmitting the presentation of the basic traditional Russian cultural humanitarian values and attitudes among foreign students, as well as for social partnership cooperation with regional authorities of the region. The developed tools in the field of forming friendly relations with foreign partners will become an element of the management system that will promote the Russian education system in international markets, form a positive image of the state and increase the level of trust in the institution of public authority. The described approaches and the practice of using the developed tools to increase institutional trust, which have been tested in the branch network of the Financial University under the Government of the Russian Federation, will form an adaptive approach to solving problems in a non-linear reality.